The Impact of Technological Innovativeness on the Intention to Utilize Digital Transformation: An Application of Diffusion of Innovation in the Egyptian Private Universities - Soliman, Dalia Samy Abdelazeem; Shalaby, Rasha Abd El Aziz Youssef; Khourshed, Nevien; Amara, Dalia Fahmy (The Arab Journal of Administration, 2024)
The purpose of this research is to empirically examine the impact of diffusion of innovation (DOI) on adoption intention to utilize Digital Transformation (DT), as well as to examine the moderation role of gender and education level between diffusion of innovation and adoption intention to utilize DT. The objectives of this research are: to examine how DOI affects adoption intention to utilize DT in the Egyptian private universities, to identify how DOI affects technological innovativeness in the Egyptian private universities, to investigate how technological innovativeness affects adoption intention to utilize DT in the Egyptian private universities, to test the mediation role of technological innovativeness in the relationship between DOI and adoption intention to utilize DT in the Egyptian private universities, to identify the most influential barriers affecting DT adoption in the Egyptian private universities and to develop a framework for the relationship between DOI on adoption intention to DT with mediating role of technological innovativeness in the Egyptian private universities using structural equation modelling. This research used a quantitative analysis by using a questionnaire tool to gather required data and structural equation model analyses (SEM) using AMOS software. The results found that all hypotheses are supported. And the mediation effect indicates that there is partial mediation effect of the technological innovativeness between diffusion of innovation and adoption intention to utilize DT in the Egyptian private universities.